Qualitative Research via Focus Groups: Will Going Online Affect the Diversity of Your Findings?. (February 2021) - Richard, Brendan; Sivo, Stephen A.; Orlowski, Marissa; Ford, Robert C.; Murphy, Jamie; Boote, David N.; Witta, Eleanor L.
Practitioners and researchers are conducting more focus groups online as a qualitative data collection method, yet rigorous methodological studies investigating the diversity of findings versus traditional in-person focus groups are limited. Previous studies primarily focused on health topics, varied on topic scope (broad to sensitive), format (synchronous vs. asynchronous), and online platform (several no longer exist). This experimental study sought to address that gap by randomly assigning participants into treatment groups to brainstorm sustainable practices for the hospitality industry (i.e., a broad topic) on a popular publicly available platform (i.e., Reddit). Although the in-person focus groups generated a greater word count and number of ideas, they generated an equivalent number of unique ideas. In terms of idea diversity, thematic analysis revealed a relatively high degree of overlap in themes from both groups. Of 13 themes, 10 (77%) occurred in both treatment groups. The overlapping themes represented 91% of all key words generated across both groups. These results highlight the potential for online focus groups to generate idea diversity at a level that is comparable to in-person focus groups. For practitioners seeking to benefit from guest insights, the findings help to substantiate the value of a lower cost, faster-to-market data collection method.